THE EFFECT OF WORK STRESS AND INDIVIDUAL CHARACTERISTICS ON EMPLOYEE PERFORMANCE AT PT MITRA AGRO SERVINDO MEDAN - Ahmad Reezky Ananda; Nur Aisyah; Sjahrir Effendy (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research get the result thatthat if the variable work stress (X1) and individual characteristics (X2) simultaneously have a value of zero, then employee performance (Y) will have a value of 17.226, if work stress variable (X1) increases by one unit, then employee performance (Y ) will increase by 0.432 units and if the individual characteristic variable (X2) increases by one unit, then employee performance (Y) will increase by 0.178 units. The Job Stress variable has a tcount of -0.798. This value is smaller than the ttable value (-0.798 <1.659) with a Sig. which is greater than 0.05 (0.432 > 0.05). This shows that partially, work stress variable does not have a significant effect on the performance of employees of PT Mitra Agro Servindo. The Individual Characteristics variable has a tcount of 1.384. This value is smaller than the ttable value (1.384 > 1.659) and is positive with a Sig value. which is smaller than 0.178 (0.021 > 0.05). This shows that partially, individual characteristic variables do not have a significant effect on the performance of employees of PT Mitra Agro Servindo. These results indicate that the variables of job stress and individual characteristics have an influence of 9.3% on the performance of employees of PT Mitra Agro Servindo while the remaining 90.7% is explained by other variables not examined in this study. individual characteristic variables do not have a significant effect on the performance of employees of PT Mitra Agro Servindo. These results indicate that the variables of job stress and individual characteristics have an influence of 9.3% on the performance of employees of PT Mitra Agro Servindo while the remaining 90.7% is explained by other variables not examined in this study. individual characteristic variables do not have a significant effect on the performance of employees of PT Mitra Agro Servindo. These results indicate that the variables of job stress and individual characteristics have an influence of 9.3% on the performance of employees of PT Mitra Agro Servindo while the remaining 90.7% is explained by other variables not examined in this study.